Non-verbal communication and writing: exploring writing anxiety in the writing process through kinesics / Norhartini Aripin and Noor Hanim Rahmat - Aripin, Norhartini; Rahmat, Noor Hanim (2019)
The 4IR teaching and learning strategies motivate learners to construct new knowledge and skills by using their cognitive domain. The aim is to encourage learners to be competent and eligible for workplace. Hence, to successfully prepare learners for that purpose, one of the soughtafter skills called writing skill should be equipped in them. Writing process actively involves verbal communication and non-verbal communication. Non-verbal communication such as kinesics is important in a writing process. Kinesics provides additional messages obtained from writers’ gesture, body movement and facial expression. This study explores the influence of kinesics on writing process and how it can be related to writing anxiety of ESL writers. Purposive sampling wasconducted to obtain pertinent samples for this study. A Video of writer’s writing process was recorded and transcribed. Results of this study provide useful implication towards teaching and learning of ESL academic writing.